The Influence of Entrepreneurship Education on Entrepreneurial Intention of University Students in China - Xing, Qianyun (2016)
Research and practical economic development have shown that entrepreneurship performs as a crucial dynamic force to economic growth. Government and policy makers have realised the importance of entrepreneurship and introduced policies to encourage entrepreneurship accordingly. Most literature indicate that entrepreneurship education has positive impact on entrepreneurial intention. Thus, entrepreneurship education is usually adopted as the best way to stimulated entrepreneurial intention, especially for university students. However, in the context of China, entrepreneurship education exists in a totally different economic environment with developed countries where entrepreneurship emerged and developed. Entrepreneurship education in China faces many new difficulties and barriers. Therefore, the study on the impact of entrepreneurship education has its implication for theories and practice. Semi-structured interview was conducted in this study to understand the perception of entrepreneurship of students in a university in Southeast China. Empirical data implies that entrepreneurship education has insignificant influence on entrepreneurial intention of university students.